Reliability of measuring half-cycle cervical range of motion may be increased using a spirit level for calibration. (February 2018) - Wilke, Jan; Niederer, Daniel; Vogt, Lutz; Banzer, Winfried
Abstract: Background: Assessments of range of motion (ROM) represent an essential part of clinical diagnostics. Ultrasonic movement analyses have been demonstrated to provide reliable results when analyzing complete amplitudes (e.g., flexion-extension). However, due to subjective determination of the starting position, the assessment of half-cycle movements (e.g, flexion only) is less reproducible. Objectives: The present study aimed to examine the reliability of measuring half-cycle cervical ROM using a spirit level for calibration. Method: 20 healthy subjects (30 ± 12yrs, 7♂, 13♀) participated in the randomized, controlled, cross-over trial. In two testing sessions with one week of wash-out in between, cervical ROM was measured by means of an ultrasonic 3D movement analysis system using a test-retest design (baseline and 5 min post baseline). The sessions differed with reference to the mask carrying the ultrasound markers. It was removed during the 5 min break (mask off) or not (mask on). To determine the resting position, a bull's eye spirit level was used in each measurement. Results: With ICC values of 0.90–0.98 (mask on, p < 0.001) and 0.90 to 0.97 (mask off, p < 0.001), both examined conditions demonstrated excellent test-retest reliability for separating the cycles regarding all movement planes. Conclusion: Cervical ROM during half-cycle movements can be assessed with excellent reliability using a spirit level. In contrast to subjective determination of the starting position, analyzing complete movement planes does not increase reliability. Using a defined and objective zero positioning allows the evaluation of repositioning tasks.